The 85th Anniversary of the Department of Pediatrics of the Russian Medical Academy of Continuous Professional Education: From Past to Future - Irina N. Zakharova; Andrei L. Zaplatnikov; Nadezhda L. Vlasova; Oksana V. Mikheeva; Mariya V. Vlasova (Union of pediatricians of Russia, 2018)
.